Stunting Prevention Intervention In Pregnant Women In 2023 - Siti Sri Wahyuni; Maryati Sutarno (International Journal of Health and Pharmaceutical (IJHP), 2024)
Stunting is a disorder of growth and development of children due to chronic malnutrition and repeated infections, which are characterized by their length or height being below standard. Malnutrition-free children are a commitment with the world, including Indonesia. The international world's commitment, contained in the second point of the Sustainable Development Goals, emphasizes the importance of "ending hunger, achieving food security and improving nutrition, and promoting sustainable agriculture". To achieve this goal, tackling the problem of malnutrition, including malnutrition, needs to be improved. Toddlers with malnutrition have short and long term impacts, in the form of growth and development disorders, including impaired cognitive function, morbidity, risk of degenerative diseases in the future and death. Stunting can be prevented early on during pregnancy, one of the interventions is good nutrition during pregnancy. Knowledge of nutrition during pregnancy isimportant for pregnant women to prevent stunted children from being born. Many pregnant women do not pay attention to nutritional intake during pregnancy so that their child can be born with stunting. Therefore, every pregnant woman must know about good nutritional intake during pregnancy to prevent stunting.